2021
DOI: 10.1002/hyp.14338
|View full text |Cite
|
Sign up to set email alerts
|

Improving WRF‐Hydro runoff simulations of heavy floods through the sea surface temperature fields with higher spatio‐temporal resolution

Abstract: This study investigates the impact of the spatio-temporal accuracy of four different sea surface temperature (SST) datasets on the accuracy of the Weather Research and Forecasting (WRF)-Hydro system to simulate hydrological response during two catastrophic flood events over the Eastern Black Sea (EBS) and the Mediterranean (MED) regions of Turkey. Three time-variant and high spatial resolution external SST products (GHRSST, Medspiration and NCEP-SST) and one coarse-resolution and timeinvariant SST product (ERA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Studies addressing ocean and groundwater feedback on hydrological processes presented more evident improvements. Kilicarslan et al (2021) showed that higher space–time resolution of SST representation as a lower boundary condition to a hydrometeorological modelling chain significantly improved flow hydrographs for the analysed heavy floods, with an RMSE reduction of up to 20%. Papaioannou et al (2021) found that accounting for the sea surface roughness in their coupled modelling framework led to an increase in the peak discharge values and an improvement in inundation forecast by 4.5% for a flash flood event.…”
Section: Contributionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies addressing ocean and groundwater feedback on hydrological processes presented more evident improvements. Kilicarslan et al (2021) showed that higher space–time resolution of SST representation as a lower boundary condition to a hydrometeorological modelling chain significantly improved flow hydrographs for the analysed heavy floods, with an RMSE reduction of up to 20%. Papaioannou et al (2021) found that accounting for the sea surface roughness in their coupled modelling framework led to an increase in the peak discharge values and an improvement in inundation forecast by 4.5% for a flash flood event.…”
Section: Contributionsmentioning
confidence: 99%
“…Kilicarslan et al (2021) applied an uncoupled high‐resolution hydrometeorological modelling chain to two catastrophic events in the Anatolian peninsula, varying the atmospheric model lower boundary conditions according to the four sea surface temperature (STT) datasets with different space–time accuracy. Even though the study aimed to evaluate the reproducibility of the hydrological response in some small, orographically complex coastal catchments, the impact of SST representation on precipitation was preliminary analysed.…”
Section: Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A critical aspect of our study involves delving into four pivotal parameters: the infiltration factor (REFKDT), surface retention depth (RETDEPRT), surface roughness (OVROUGHRT), and channel roughness (MannN). Prior research has underscored the significance of these parameters in the nuanced calibration and optimization of the model to capture hydrological responses accurately, especially in scenarios characterized by extreme rainfall and flooding events [16][17][18][19][20]. While previous studies have conducted numerous simulations in various global regions, the utilization of the WRF-Hydro model in the MATOPIBA region of Brazil remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…treme rainfall and flooding events [16][17][18][19][20]. While previous studies have conducted numerous simulations in various global regions, the utilization of the WRF-Hydro model in the MATOPIBA region of Brazil remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%